Analysis of cassine and spectaline in the Senna spectabilis ethanolic extracts by capillary zone electrophoresis with indirect UV detection - Barbosa, Marilia Fontes; Pivatto, Marcos; Cardoso, Arnaldo Alves [UNESP]; da Silveira Petruci, João Flávio (Wiley, 2024)
Introduction: 2,6-Disubstituted piperidin-3-ols are an important group of piperidine alkaloids found in species such as Senna spectabilis, whose main constituents include cassine and spectaline, compounds with relevant pharmacological activity. The analysis of these compounds is challenging due to the complexity of plant extracts and the absence of chromophores capable of absorbing ultraviolet (UV) radiation. Objective: This paper presents a new analytical method to separate and quantify the non-UV-absorbing alkaloids present in ethanol extracts from S. spectabilis flowers using capillary zone electrophoresis (CZE) with indirect UV detection. Methodology: The optimized CZE method employs a background electrolyte containing 60 mM histidine (His), 15 mM α-cyclodextrin, 20% acetonitrile (ACN), and pH-adjusted to 4.7 with acetic acid (AcOH). Results: The limit of detection (LOD) values was 10.2 and 13.9 mg L−1 for cassine and spectaline, respectively. For both analytes, the precision data were better than 2% of relative standard deviation (RSD) for migration times and peak areas. To evaluate the applicability of the developed method, ethanolic extracts from S. spectabilis flowers were prepared and analyzed. Conclusions: Thereby, the method proved to be efficient and complementary to conventional techniques, offering a cost-effective alternative in the quantification of the non-UV-absorbing piperidine alkaloids present in plant extracts.
Keywords: capillary zone electrophoresis; indirect UV detection; non-UV-absorbing piperidine alkaloids; Senna spectabilis